Socialization of the Introduction and Utilization of Sapodilla Fruit Juice as a Traditional Medicine for Patients with Diabetes Mellitus in Lubuk Pakam - Novandi Purba; Nur Ulina Turnip; Sari Desi Esta Ulina Sitepu; Selamat Tuahta Sipayung (JURNAL PENGMAS KESTRA (JPK), 2026)
Diabetes Mellitus (DM) is a chronic metabolic disease characterized by elevated blood glucose levels due to impaired insulin secretion, insulin action, or both. The increasing prevalence of DM requires community-based promotive and preventive efforts, including the use of natural ingredients as supporting traditional treatments. Sapodilla fruit (Manilkara zapota) is known to contain dietary fiber, polyphenols, flavonoids, and antioxidant compounds that have the potential to help control blood sugar levels. This community service activity aims to increase the knowledge and understanding of DM sufferers regarding the introduction and use of sapodilla fruit juice as a complementary traditional therapy. The methods used included outreach, health education, cooking sapodilla fruit juice, and interactive discussions. The results of the activity showed a significant increase in participants' knowledge levels. The "good" knowledge category increased from 16.7% before the activity to 73.3% after the activity. In addition, participants showed a positive attitude towards the use of sapodilla fruit juice as a safe complementary therapy without replacing primary medical treatment. This activity is expected to become an alternative, applicable and sustainable health education to support the healing of Diabetes Mellitus in the community.